(untitled) (Cardiovascular Journal, 2011)
Complementary and alternative medicine (CAM) refers to a broad set of health care practices that are not part of a country’s own tradition and are not integrated into the dominant health care system. Herbal remedies, dietary supplements, acupuncture, homeopathy, ayurveda, unani, traditional Chinese medicine, prayer, yoga and meditation are the common examples. CAM therapies often represent an enormous area of unregulated and widely practised therapeutics with an inadequate scientific literature. However, there is emerging evidence that some of the CAM therapies are effective in certain clinical conditions. Presently, throughout the world, there is rampant growth of CAM industries, and increasing number of reputed pharmaceutical companies are producing herbals and dietary supplements. Herbal products used for cardiovascular purposes include garlic, hawthorn, ginkgo, horse chestnut and arjun. These substances are often popularly believed to be ‘natural’, hence safe. But adverse reactions including deaths have been reported with some of the CAM products. There is also growing concern for significant drug interaction among commonly used herbals, dietary supplements and cardiovascular drugs. At present, CAM therapies may best be regarded as an adjunct to standard medical care. More scientific research and strict regulation by standard national and international authorities are needed to ensure their efficacy and safety in cardiovascular care. Key words: Complementary and alternative medicine, Herbals, Cardiovascular care. DOI: http://dx.doi.org/10.3329/cardio.v1i1.8211 Cardiovasc. j. 2008; 1(1) : 84-96